Peningkatan Kemampuan Pemahaman Matematis Dan Penalaran Matematis Melalui Problem Based Learning (PBL) Siswa Sekolah Menengah Pertama - ., Topik (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2015)
The research aims to studyof improvement mathematical understanding and mathemacal reasoning. The design researchis control group non-equivalen pretest and posttest. The population of all private secondaryschool in west bandung. The selection of a cluster sampling (area sampling) i.e. eighth classprivate secondary boarding school Darun Nasya. The instrument used are mathematicalunderstanding, mathemacal reasoning and observation sheets. The analysis of quantitativedatum using two way anova test. Research results : (1) there was no difference inimprovement of the ability of mathematical understanding; (2) there is a deffernce inmathematical reasoning ability improvement; (3) there is a defference in mathematicalreasoning ability improvement KAM among group with KAM hight group, the other groupthere is no defference; (4) there is no intreraction between the learning model and KAM toimprovement ability mathematical understanding, mathemacal reasoning